The role of photobiomodulation in the functional recovery of proximal humerus fractures: a randomized controlled clinical protocol - Luiz Claudio de Freitas; Do Sung Kim; Daniel Santana da Costa; Henrique Pellacani Fernandes Soutello; Thiago Roncoletta Salata; Luis Fumio Sato; Nilton Iuichi Takahashi; Valenthin de Souza Gomes; Priscila Terumi Kondo; Gustavo Guedes Lomonaco; Bruno Ricardo Trigo; Cinthya Cosme Gutierrez Duran; et al. (PLoS ONE, 2025)
Pain and joint stiffness contribute to functional limitation in the postoperative period following proximal humeral fractures (PHF). Photobiomodulation (PBM) has demonstrated positive outcomes in fracture repair, analgesia, and functional improvement, as evidenced by randomized controlled trials (RCTs) and experimental animal studies. Clinical studies have shown PBM’s efficacy in reducing pain and improving functional outcomes, while preclinical studies have demonstrated enhanced bone regeneration through PBM application. This clinical study is a randomized, double-blind, controlled trial to investigate the effects of PBM on the shoulder functional recovery after proximal humerus fractures. A total of forty-two participants, aged 18–65 years of both genders, will be randomly divided into two groups: the Control group (receiving physiotherapy combined with simulated PBM) and the PBM group (receiving physiotherapy combined with active PBM). The PBM application (10 minutes) will be performed daily by the participants at home, using a device equipped with 318 light-emitting diodes (LEDs), consisting of 159 LEDs at 660 nm (28.5 mW; 12 J/cm²; 17 J per LED) and 159 LEDs at 850 nm (23 mW; 10 J/cm²; 14 J per LED). The PBM sessions, along with physiotherapy sessions (30 minutes, twice weekly), will be conducted over a 12-week period. Participants will be blinded to their group allocation and will be assessed by a single evaluator at 24 hours, 1 week, 2 weeks, 4 weeks, 8 weeks, and 12 weeks post-surgery. The evaluator will also be blinded to the participants’ group assignments. The primary outcome will be shoulder functional recovery after proximal humerus fractures, assessed using the Quick-DASH scale at all experimental time points. Secondary outcomes will include range of motion (measured with a digital goniometer), quality of life (evaluated using the SF-6D questionnaire), pain on pressure and the incidence of adverse effects, all assessed at each time point. Spontaneous pain, nocturnal pain and analgesic use will be evaluated over a 12-week period. Fracture consolidation will be assessed through radiography at weeks 4, 8, and 12. Muscle strength will be measured through dumbbell lifting at weeks 8 and 12. If the data are normally distributed, ANOVA will be used, and results will be presented as means ± standard deviation (SD). If the data are not normally distributed, they will be presented as medians and interquartile ranges, with comparisons made using non-parametric tests. A p-value of less than 0.05 will be considered statistically significant.